CDKN2A and BAP1 germline mutations predispose to melanoma and mesothelioma. Issue 2 (10th August 2016) - Betti, M.; Aspesi, A.; Biasi, A.; Casalone, E.; Ferrante, D.; Ogliara, P.; Gironi, L.C.; Giorgione, R.; Farinelli, P.; Grosso, F.; Libener, R.; Rosato, S.; et al.
Highlights: Melanoma and mesothelioma show a statistically significant co-occurrence in the general population. Inherited melanoma and mesothelioma predisposition is shown by individual with germline mutations in BAP1 . We report a patient with mesothelioma who carried a germline mutation in CDKN2A, a gene involved in familial melanoma. This paper suggests that CDKN2A and possibly other genes may also predispose to both these tumors. It also suggests that mesothelioma and melanoma may share common stepwise carcinogenic pathways. Abstract: BAP1 germline mutations predispose to a cancer predisposition syndrome that includes mesothelioma, cutaneous melanoma, uveal melanoma and other cancers. This co-occurrence suggests that these tumors share a common carcinogenic pathway. To evaluate this hypothesis, we studied 40 Italian families with mesothelioma and/or melanoma. The probands were sequenced for BAP1 and for the most common melanoma predisposition genes (i.e. CDKN2A, CDK4, TERT, MITF and POT1 ) to investigate if these genes may also confer susceptibility to mesothelioma. In two out of six families with both mesothelioma and melanoma we identified either a germline nonsense mutation (c.1153C > T, p.Arg385*) in BAP1 or a recurrent pathogenic germline mutation (c.301G > T, p.Gly101Trp) in CDKN2A . Our study suggests that CDKN2A, in addition to BAP1, could be involved in the melanoma and mesothelioma susceptibility, leading to the rare familial cancer syndromes. It also suggests that these tumors share key steps that drive carcinogenesis and that other genes may be involved in inherited predisposition to malignant mesothelioma and melanoma.